Crystal Structures of the p21-activated kinases PAK4, PAK5, and PAK6 reveal catalytic domain plasticity of active group II PAKs - Eswaran, J; Lee, W; Debreczeni, J; Filippakopoulos, P; Turnbull, A; Fedorov, O; Deacon, S; Peterson, J; Knapp, S (Cell Press, 2007)
p21-activated kinases have been classified into two groups based on their domain architecture. Group II PAKs (PAK4-6) regulate a wide variety of cellular functions, and PAK deregulation has been linked to tumor development. Structural comparison of five high-resolution structures comprising all active, monophosphorylated group II catalytic domains revealed a surprising degree of domain plasticity, including a number of catalytically productive and nonproductive conformers. Rearrangements of helix alphaC, a key regulatory element of kinase function, resulted in an additional helical turn at the alphaC N terminus and a distortion of its C terminus, a movement hitherto unseen in protein kinases. The observed structural changes led to the formation of interactions between conserved residues that structurally link the glycine-rich loop, alphaC, and the activation segment and firmly anchor alphaC in an active conformation. Inhibitor screening identified six potent PAK inhibitors from which a tri-substituted purine inhibitor was cocrystallized with PAK4 and PAK5.